2010
DOI: 10.1103/physrevb.81.132502
|View full text |Cite
|
Sign up to set email alerts
|

Correlated flux noise and decoherence in two inductively coupled flux qubits

Abstract: We have studied decoherence in a system where two Josephson-junction flux qubits share a part of their superconducting loops and are inductively coupled. By tuning the flux bias condition, we control the sensitivities of the energy levels to flux noises in each qubit. The dephasing rate of the first excited state is enhanced or suppressed depending on the amplitudes and the signs of the sensitivities. We have quantified the 1/f flux noises and their correlations and found that the dominant contribution is by l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 31 publications
(31 reference statements)
4
42
0
Order By: Relevance
“…The result (12) is equivalent to the explicit subtraction of the incoherent noise S n from S k (Eqs. 6,8), with the advantage, however, of drastically reduced uncertainty, in particular at high frequencies where the (1/f -noise) signal is much smaller than the white noise. This method is appropriate for the analysis of, e.g., 1/f -type noise.…”
Section: Cross-psd: White-noise Eliminationmentioning
confidence: 99%
See 2 more Smart Citations
“…The result (12) is equivalent to the explicit subtraction of the incoherent noise S n from S k (Eqs. 6,8), with the advantage, however, of drastically reduced uncertainty, in particular at high frequencies where the (1/f -noise) signal is much smaller than the white noise. This method is appropriate for the analysis of, e.g., 1/f -type noise.…”
Section: Cross-psd: White-noise Eliminationmentioning
confidence: 99%
“…We just have to replace the mean-square b 2 by the variance σ 2 b and set δ(f k ) = δ k,0 ∆t to obtain Eq. (8).…”
Section: White-noise Floormentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra typically follow 1/f frequency dependence with a spectral density of 1-10 μ 0 / √ Hz at 1 Hz, where 0 = h/2e is the superconducting flux quantum. The accessible frequency range of the PSD was limited to approximately 10 MHz in spin-echo measurements [4,5,9,15] and was extended to a few tens of megahertz using Carr-Purcell-Meiboom-Gill pulse sequences [9]. Recently, spin-locking measurements provided the PSD up to approximately 100 MHz [16], and a study of qubit relaxation due to dressed dephasing in a driven resonator revealed the PSD at approximately 1 GHz [17].…”
mentioning
confidence: 99%
“…This value has not changed in order of magnitude since the first measurements of flux noise in the 1980's; 3,4 only minor improvements are observed in modern devices. [5][6][7][8][9][10] While flux noise is sufficiently low for several applications, it is still considered a barrier for the use of the SQUID as a quantum bit (the flux qubit) in a superconductor-based quantum computer architecture.…”
Section: Introductionmentioning
confidence: 99%